FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT PADA INSPEKTORAT PROVINSI SULAWESI UTARA - Turangan, Grace M.; Karamoy, Herman; Tinangon, Jantje J. (ACCOUNTABILITY, 2016)
The purpose of this research is to examine the effect of the competence, experience, independence, objectivity, integrity and motivation auditor in North Sulawesi Provincial Inspectorate to audit quality. The study population was all auditors in Inspectorate of North Sulawesi province with a total sample of 60 auditors working in the Inspectorate of North Sulawesi province. The sampling technique used purposive approach / judgment sampling. The results of multiple regression analysis explains that the quality of the audit which is owned by the Inspectorate of North Sulawesi associated positively or direction of the competence, experience, independence, objectivity, integrity and motivation. the results of the study to simultaneously show that variables, Competence, experience, independence, objectivity, integrity and motivation together significantly influence the variable quality of the audit. While in partial competence, experience and independence not significant effect on audit quality otherwise variable objectivity, integrity and motivation have a significant effect on audit quality. The correlation coefficient (R) of 0.803 indicates that the relationship between competence, experience, independence, objectivity, integrity and motivation have a relationship (correlation) is very strong on audit quality, as it approaches a value of 1. The value of adjusted R2 as the coefficient of determination is 0.605, which means improvement of audit quality by 60.5% influenced by competence, experience, independence, objectivity, integrity and motivation, while the remaining 39.5% is influenced by other factors outside the research or explained by other variables not included in this study. Key Words :     Audit quality, competence, experience, independence, objectivity, integrity and motivation.